2006
DOI: 10.1007/s00411-006-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accumulation of 137Cs and 90Sr by six spring wheat varieties

Abstract: The uptake of (137)Cs and (90)Sr by six varieties of spring wheat (Triticum aestivum) was compared in field trials on land contaminated by the Chernobyl accident. All the experimental varieties are officially adopted for agricultural use in Belarus and are used in large-scale production. Under identical conditions of nutrition, the productivity of the varieties varied significantly by a factor of 1.3. The extent of (137)Cs and (90)Sr accumulation by wheat grain, quantified as the concentration ratio, differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Among distinct varieties of wheat and maize a genetic variation in Cs + enrichment was observed by a factor of 1.5–3.1 (Schimmack et al , 2004; Putyatin et al , 2006; Schneider et al , 2008). Similar to this study, Payne et al (2004) detected a natural genetic variation in Cs + concentration by a factor of 2 in shoots of Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among distinct varieties of wheat and maize a genetic variation in Cs + enrichment was observed by a factor of 1.5–3.1 (Schimmack et al , 2004; Putyatin et al , 2006; Schneider et al , 2008). Similar to this study, Payne et al (2004) detected a natural genetic variation in Cs + concentration by a factor of 2 in shoots of Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…For Sr 2+ , the genetic variation for enrichment was monitored as well. Within different wheat varieties, a 1.6–2.6-fold variation in Sr 2+ concentration was detected (Gerstmann and Schimmack, 2006; Putyatin et al , 2006). To date, no comparable data about Sr 2+ concentration have been available for Arabidopsis thaliana shoots, but the ascertained natural variation of a factor of 2.1 fitted to the data known for other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this was not the case for oats. Rasmusson et al (1963) found that the barley (H. vulgare) variety with the lowest (Podolyak, 2007); (þ ¼ Meadow clover (Podolyak, 2007); D ¼ Pea (Shirshov and Shain, 1971); # ¼ Potato (Green et al, 1996); ⊠ ¼ Wheat grain (Putyatin et al, 2006); -¼ Wheat straw (Putyatin et al, 2006); , ¼ White clover (Podolyak, 2007) and (b) stable caesium and strontium concentrations in plants (-¼ Brassica oleracea (Bibak et al, 1999); : ¼ Lettuce (Melnitchouck and Hodson, 2004); * ¼ Onion (Ariyama et al, 2006)). Note that only concentration ratio data are shown on this graph e there are additional activity concentration data.…”
Section: Plant Partsmentioning
confidence: 98%
“…Recent studies on the root uptake of fallout 90 Sr and 137 Cs by various wheat cultivars have demonstrated considerable differences between the cultivars (Schimmack et al, 2004;Gerstmann and Schimmack, 2006;Putyatin et al, 2006). These studies were aimed at finding wheat cultivars with minimum root uptake of radionuclides in order to use them on areas highly contaminated by radionuclides as present in the 30 km zone of the Chernobyl power plant since 1986.…”
Section: Introductionmentioning
confidence: 98%